2010
DOI: 10.1215/1089201x-2010-038
|View full text |Cite
|
Sign up to set email alerts
|

The Indo-Mediterranean Caduceus and the Worship of the Tree, the Serpent, and the Mother Goddess in the South of India

Abstract: C o m p a r a t i v e S t u d i e s o f S o u t h A s i a , A f r i c a a n d t h e M i d d l e E a s t V o l . 3 0 , N o . 3 , 2 0 1 0 d o i 1 0 .1 2 1 5 / 1 0 8 9 2 0 1 x -2 0 1 0 -0 3 8 © 2 0 1 1 b y D u k e U n i v e r s i t y P r e s s 6 1 0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Interestingly, the proportion of species that are planted appears unrelated to the age of the church or the size of its forest, as some of the oldest and largest forests include many cultivated species. The number of planted species is higher than previous studies in other parts of Ethiopia, where only exotic species have been reported as planted (Wassie et al 2005, 2010, Aerts et al 2006. However, it is unclear whether researchers have asked local people about the cultivation status of indigenous species.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Interestingly, the proportion of species that are planted appears unrelated to the age of the church or the size of its forest, as some of the oldest and largest forests include many cultivated species. The number of planted species is higher than previous studies in other parts of Ethiopia, where only exotic species have been reported as planted (Wassie et al 2005, 2010, Aerts et al 2006. However, it is unclear whether researchers have asked local people about the cultivation status of indigenous species.…”
Section: Discussionmentioning
confidence: 64%
“…A recent survey of 348 church forests across northern and central Ethiopia (Aerts et al 2016) found that most are relatively small (2.48 ± 0.24 ha). Nonetheless, ecologists have conducted numerous studies showing that church forests harbour species that are rare in the rest of the landscape and therefore contribute to biodiversity conservation at local and regional scales (Wassie et al 2005, 2010, Aerts et al 2006, Mulat 2013, Meshesha et al 2015.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The woman is represented as being able to conceive because she has first been ritually wedded to a tree or has been chosen as the fitting receptacle for a spirit that is ready to be born into this material world. 29 A woman is able to bear a child for what she is herself: a vessel for the forces of life, not because of any biological process dependent upon a male partner. The need a woman might have to find a husband is unrelated to her power to conceive.…”
mentioning
confidence: 99%